Evaluasi dan Perancangan Ulang UI/UX Aplikasi GoDentist Menggunakan Metode Double Diamond - Susilowati, Merliana Tri; Umbara, Fajri Rakhmat; Ilyas, Ridwan (METIK JURNAL (AKREDITASI SINTA 3), 2025)
GoDentist is a teledentistry application that supports dental healthcare services. Based on initial observations and evaluations using the User Experience Questionnaire (UEQ), issues were identified in the aspects of perspicuity, dependability, and novelty, such as monotonous design, confusing navigation, and features that did not meet user expectations. This study aims to evaluate and redesign the user interface (UI/UX) of the GoDentist application using the Double Diamond method, which consists of four stages: Discover, Define, Develop, and Deliver, integrated with UEQ and A/B Testing. The evaluation involved 100 respondents aged 15–58 years, the majority of whom were 18–35 years old with adequate digital literacy. Initial results showed low scores in perspicuity, dependability, and novelty. After redesign and prototyping, novelty increased from 0.49 to 1.62, perspicuity from 0.57 to 1.75, and dependability from 0.76 to 1.91. A/B Testing revealed that 59.08% of respondents preferred the new design. These findings indicate that integrating the Double Diamond method with UEQ and A/B Testing can significantly enhance user experience perceptions in terms of both aesthetics and functionality.